Digoxin Therapy of Fetal Superior Ventricular Tachycardia: Are Digoxin Serum Levels Reliable? - Saad, Antonio F.; Monsivais, Luis; Pacheco, Luis D. (American Journal of Perinatology Reports, 2016)
Background Despite its seldom occurrence, fetal tachycardia can lead to poor fetal outcomes including hydrops and fetal death. Management can be challenging and result in maternal adverse effects secondary to high serum drug levels required to achieve effective transplacental antiarrhythmic drug therapy.Case A 33-year-old woman at 33 weeks of gestation with a diagnosis of a fetal sustained superior ventricular tachycardia developed chest pain, shortness of breath, and bigeminy on electrocardiogram secondary to digoxin toxicity despite subtherapeutic serum drug levels. She required supportive care with repletion of corresponding electrolyte abnormalities. After resolution of cardiac manifestations of digoxin toxicity, the patient was discharged home. The newborn was discharged at day 9 of life on maintenance amiodarone.Conclusion We describe an interesting case of digoxin toxicity with cardiac manifestations of digoxin toxicity despite subtherapeutic serum drug levels. This case report emphasizes the significance of instituting an early diagnosis of digoxin toxicity during pregnancy, based not only on serum drug levels but also on clinical presentation. In cases of refractory supportive care, digoxin Fab fragment antibody administration should be considered. With timely diagnosis and treatment, excellent maternal and perinatal outcomes can be achieved.
Keywords: pregnancy; fetal SVT; digoxin; toxicity